Taxpayer compliance level; influencing demographic factors - Sulestiyono, Deddy; Aresteria, Maya; Rakhmayani, Alfita (Proceeding International Conference on Accounting and Finance, 2024)
This research aims to find out how demographic factors influence the perception of compliance with MSME tax obligations. Data collection was carried out by distributing questionnaires and a sample size of 100 respondents. This research was conducted in Semarang City. Demographic factors studied include gender, age, education level, and income level. The results of this study show that male and female respondents have the same tax compliance, while age, education level and income level have an influence on the perception of MSME tax compliance.